PROBLEMS OF DEVELOPING A RESPECTFUL ATTITUDE TOWARDS INTELLECTUAL PROPERTY IN THE REPUBLIC OF UZBEKISTAN - Saidov Akmal Kholmatovich; Okyulov Omonboy (American Journals, 2023)
This scientific article analyzes the relationship between the motivational foundations of people’s behavior and respectful attitudes towards compliance with the requirements of intellectual property legislation. In particular, the authors studied the following motivational postulates: respects when he knows, respects when there are interests, respects when he is afraid, respects when partners respect, respects when everyone respects. The study substantiates the conclusion that it is impossible to either absolutize or ignore each of these postulates. Not only in legislative activities, but also in the development and implementation of the Strategy for the Development of Intellectual Property of the country, it is imperative to take into account these motivational foundations of people’s behavior in a differentiated form.
Keywords: Intellectual property, copyright holder, piracy, public policy, strategy for the development of intellectual property, motivation for law-abidingness, legal culture, legal consciousness, inevitability of responsibility.